HER2-targeted therapies for HER2-positive early-stage breast cancer: present and future - Xu, Luying; Xie, Yuxin; Gou, Qiheng; Cai, Rui; Bao, Rong; Huang, Yucheng; Tang, Ruisi (Frontiers in Pharmacology, 2024)
Breast cancer (BC) has the second highest incidence among cancers and is the leading cause of death among women worldwide. The human epidermal growth factor receptor 2 (HER2) is overexpressed in approximately 20% to 30% of BC patients. The development of HER2-targeted drugs, including monoclonal antibodies (mAbs), tyrosine kinase inhibitors (TKIs) and antibody-drug conjugates (ADCs), has improved the operation rate and pathological remission rate and reduced the risk of postoperative recurrence for HER2-positive early-stage BC (HER2+ EBC) patients. This review systematically summarizes the mechanisms, resistance, therapeutic modalities and safety of HER2-targeted drugs and helps us further understand these drugs and their use in clinical practice for patients with HER2+ EBC.